2014
DOI: 10.2459/jcm.0b013e3283649978
|View full text |Cite
|
Sign up to set email alerts
|

Should primary percutaneous coronary intervention be the routine reperfusion strategy in octogenarians presenting with ST elevation myocardial infarction?

Abstract: The mortality in our patients of at least 80 years was similar to the previously published data, despite the advances in PPCI procedures. Considering the increasing number of octogenarian patients with STEMI at the present time, there is a need for a randomized trial to compare the different treatment strategies for STEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
3
4
1
Order By: Relevance
“…The 30‐day and 1‐year mortality observed in our population is consistent with those reported in recent studies among octogenarian and nonagenarian STEMI patients . In populations similar to ours, Antonsen et al , Claessen et al , Showkathali et al , and Shah et al reported 30‐day mortality of 18%, 20%, 21%, and 25%, respectively. Newell et al reported a 1‐year mortality of 28.9% among patients age ≥80 years.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The 30‐day and 1‐year mortality observed in our population is consistent with those reported in recent studies among octogenarian and nonagenarian STEMI patients . In populations similar to ours, Antonsen et al , Claessen et al , Showkathali et al , and Shah et al reported 30‐day mortality of 18%, 20%, 21%, and 25%, respectively. Newell et al reported a 1‐year mortality of 28.9% among patients age ≥80 years.…”
Section: Discussionsupporting
confidence: 91%
“…The lower utilization of DESs among our elderly patients reflects widespread perception of the higher risk of bleeding in elderly patients and the reluctance of operators to commit elderly patients to DAPT for a prolonged period without a detailed clinical history, which is often not available for patients presenting for pPCI. Although elderly patients are less likely to receive DESs, other authors reported a higher use of DESs than ours …”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Two observational studies (2.9%) specifically recruited older patients. 10 11 A systematic review of RCTs in ACS demonstrated that the percentage of randomised trials excluding older patients appears to be falling, from 31.9% in 1996–2001 to 22.7% in 2014. 5 Indeed, although enrolment of older patients (≥75 years) has increased in recent decades, only 10.3% of patients fell into this age category in RCTs published between 1996 and 2000.…”
Section: Discussionmentioning
confidence: 99%
“…The very elderly (those ≥ 85 years of age) are the most rapidly growing population in Western countries. The mortality rate of this group increases markedly following ST-segment elevation myocardial infarction (STEMI) [ 1 , 2 ]. However, limited data are available regarding the outcomes of primary percutaneous coronary intervention (PCI) in this age group, especially in nonagenarians, who are generally excluded from clinical trials [ 3 ].…”
Section: Introductionmentioning
confidence: 99%